1995
DOI: 10.1111/j.1440-1681.1995.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

α1‐ADRENOCEPTORS ON RABBIT AORTIC SMOOTH MUSCLE CELLS IN CULTURE AND IN EXPERIMENTAL INTIMAL THICKENING

Abstract: 1. This study has defined alpha 1-adrenoceptors and their reactivity in rabbit aorta, following removal of the endothelium and formation of a myointimal thickening, and also in smooth muscle cells (SMC) in cell culture which had undergone serial passaging and changes in phenotype. 2. [3H]-prazosin binding to SMC from control aorta, vessels 2 weeks after endothelial denudation and sub-cultured SMC (passage 3-6) was specific (displaceable with 10 mumol/L phentolamine), and of high affinity to a single class of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The reasons for this disagreement are not evident, but may relate to minimal wall distension injury following simple endothelial denudation. Consistent with this, another study of balloon denudation of rabbit aorta endothelium reported that, 2 weeks later, when a small intimal thickening was present, maximal contraction to phenylephrine and potassium chloride was unchanged and potency to phenylephrine was reduced threefold 29 . It is interesting that unlike α‐AR downregulation by balloon injury, angiotensin receptors, which also mediate trophic activity on vascular SMC, are upregulated by balloon injury 30,31 …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The reasons for this disagreement are not evident, but may relate to minimal wall distension injury following simple endothelial denudation. Consistent with this, another study of balloon denudation of rabbit aorta endothelium reported that, 2 weeks later, when a small intimal thickening was present, maximal contraction to phenylephrine and potassium chloride was unchanged and potency to phenylephrine was reduced threefold 29 . It is interesting that unlike α‐AR downregulation by balloon injury, angiotensin receptors, which also mediate trophic activity on vascular SMC, are upregulated by balloon injury 30,31 …”
Section: Discussionmentioning
confidence: 63%
“…Consistent with this, another study of balloon denudation of rabbit aorta endothelium reported that, 2 weeks later, when a small intimal thickening was present, maximal contraction to phenylephrine and potassium chloride was unchanged and potency to phenylephrine was reduced threefold. 29 It is interesting that unlike a-AR downregulation by balloon injury, angiotensin receptors, which also mediate trophic activity on vascular SMC, are upregulated by balloon injury. 30,31 To begin examining possible mechanisms responsible for a-AR downregulation, we examined rat aorta SMC in early passage cell culture that express a 1B -and a 1D -AR (but not a 1A -or a 2D -AR) for an effect of FGF2 and TGF-b1 on expression.…”
Section: Discussionmentioning
confidence: 99%